A randomized pharmacokinetic and pharmacodynamic trial of two regular human insulins demonstrates bioequivalence in type 1 diabetes and availability of biosimilar insulin may improve access to this medication. Issue 8 (13th May 2022) - Vencio, Sérgio; Caiado‐Vencio, Rafael; Caixeta, Leonardo Ferreira; Masierek, Małgorzata; Mlynarski, Wojciech; Drzewoski, Józef; Gregory, Justin M.
Abstract: Aims: To compare the pharmacokinetic (PK) and pharmacodynamic (PD) effects and safety of therapeutic dosages of a regular insulin (experimental drug) produced by Bioton S.A. (Warsaw, Poland) versus Humulin® R, a regular insulin (reference drug) produced by Eli Lilly (Indianapolis, Indiana). Materials and Methods: In a single‐centre, randomized, double‐blinded phase 1 crossover study, we used the manual euglycaemic clamp technique to compare PK and PD profiles between single subcutaneous doses (0.3 units/kg) of the two regular insulins in participants with type 1 diabetes (T1DM) with a washout period of 14 (± 7) days between tests. Results: We evaluated 56 participants. The mean participant age and body mass index were 32.9 years and 22.9 kg/m 2, respectively. The ratios (experimental/reference) of the geometric means of maximum plasma insulin concentration and for plasma insulin area under the curve (AUC) were 0.909 (90% confidence interval [CI] 0.822‐1.01) and 0.993 (90% CI 0.944‐1.04), respectively. The ratios of the geometric means of maximum glucose infusion rate (GIR) and for GIR AUC were 0.999 (95% CI 0.912‐1.09) and 1.04 (95% CI 0.962‐1.12), respectively. Conclusions: The experimental product regular human insulin and comparator Humulin® R are bioequivalent in patients with T1DM. Wider entry to the pharmaceutical market of affordable, biosimilar regular insulins may substantially improve access to insulin for many socioeconomically disadvantaged patients with diabetes.